Óxido nítrico modula a melhora da memória induzida por espermidina em ratos - Guerra, Gustavo Petri (2006)
The endogenous poliaminas, putrescine, spermidina and spermine are aliphatics amines that are present in high concentrations in the central nervous system (SNC). The action of the poliamines involves the modulation of several ionic channels, including the subtype of glutamatergic N-methyl-D-aspartate receptor (NMDA). The processes mediated by NMDA receptor include synaptic plasticity and formation of neural circuitry. It is believed that these plasticities happening in some cerebral areas specifies, as the hippocampus, are critical for the learning and memory processes. It is described that spermidine (SPD), as well as the nitric oxide are directly involved with processes of formation of the memory. Therefore, we investigated the involvement of the nitric oxide in the facilitatory effect induced by SPD on the memory of males Wistar rats. For that, the rats were bilaterally cannulae in the hippocampus, after the surgical recovery, the animals were trained in the inhibitory avoidance task, injected bilaterally in the hippocampus and tested in the same task. Thirty minutes after the administration of the drugs the animals were decapitated and the nitrite and nitrate levels (NOX) they were determined in the hippocampus of the rats. The bilateral injection of 0.1 nmol of L-NAME, a non-selective inhibitor of the nitric oxide synthase, SPD (0.2 nmol) or the association of SPD and L-NAME, were achieve Immediately after the training in the inhibitory avoidance task. The administration of L-NAME didn't cause effect per se on memory and it reverted the facilitatory effect induced by SPD. Spermidine increased the levels of NOX in the hippocampus, and the coinjection of L-NAME prevented this increase induced by SPD. The systemic administration of 7-NI (30 mg/kg), a selective inhibitor of the nitric oxide synthase neuronal, 30 minutes before the training of it the inhibitory avoidance impaired the memory and didn't prevent the increase in the levels of NOX induced by SPD. None of the drugs studies altered the locomotor activity of the animals. These results suggest that the facilitatory effect of the memory induced by SPD it is mediated, at least partly, for the increase of the synthesis of the nitric oxide.